No Maunder Minimum phase in HD 4915 - Flores Trivigno, Matias Gaston (2024)
Context. The long-term solar magnetic activity and its cyclical behaviour, which is maintained by a dynamo mechanism, are both still challenging problems for astrophysics. In particular, an atypical event occurred between 1645 and 1715, when the solar activity was remarkably decreased and the number of sunspots was extremely reduced. However, the exact events that unfolded during the solar cycle remain unclear. The discovery of longer activity minima in cool stars may shed light on the nature of the complex mechanisms involved in the long-term behaviour of the solar-stellar dynamo. Aims. Our aim is to explore whether the G5V solar-like star HD 4915, which showed a striking chromospheric activity pattern in a previous study performed with HIRES data, might be considered a bona fide Maunder Minimum (MM) candidate. Methods. We analysed over 380 spectra acquired between 2003 and 2022 using the HARPS and HIRES spectrographs. We carriedout a detailed search for activity signatures in HD 4915 by using the Mount Wilson and the Balmer Hα activity indexes. This task was performed by means of the generalised Lomb-Scargle periodogram.Results. The new HARPS data show that the chromospheric activity of HD 4915 is not decreasing. In fact, the increases in the activity after the broad minimum in three years reaches the level of activity before this phase, suggesting that it is not entering an MM phase. We also calculate a rotation period of 23.4 ± 0.2 d, which has not been reported before. Conclusions. HD 4915 shows a distinctive activity behaviour that was initially attributed to a possible and incipient MM phase.Additional HARPS data allowed us to discard an MM in the star. Our analysis shows that the complex activity pattern of HD 4915 might be ruled by a multiple activity cycle, in which a shorter cycle of 4.8 yr is modulated by a potential longer cycle. More activity surveys with extensive records and suitable cadence are crucial for an accurate identification of stars in magnetic grand minima.